Literature Review: Parental Behavior in the Habit of Brushing Preschool Children's Teeth Against Early Childhood Caries - Culia Rahayu; Fredy Mulyadi; Hilmiy Ila Robbihi; Yayah Sopianah (Institute of Computer Science (IOCS), 2022)
Oral and dental health is a component of general health and is also an essential factor in the normal growth of children. Caries affecting infants, toddlers, and pre-schoolers describe a unique pattern of caries lesions called Early Childhood Caries (ECC). The purpose of this study was to describe parents' behaviour in brushing habits of preschool children against early childhood caries. This research is a literature review. The population in this study were 15,231 journals, both national and international, related to the behaviour of parents in brushing their teeth in preschool children against early childhood caries. The sample in this study was 15 journals published in 2015-2020. Based on the review literature on journals, it was found that the knowledge and skills of parents about the habit of brushing teeth, time and frequency of brushing teeth influenced early childhood caries in preschool children. Thus, the school should collaborate with the Puskemas concerning efforts to improve children's oral and dental health, which includes counselling on how to brush teeth properly, when brushing teeth and routine check-ups at the Puskesmas or the dentist.